2021
DOI: 10.1111/jocn.15721
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care needs and associated factors among patients with ostomy: A Cross‐Sectional Study

Abstract: Aims and objectives To investigate the spiritual care needs and associated factors in patients with ostomy. Background The significance of the spiritual care needs of the patients has been emphasised across countries and cultures in the literature. Design A descriptive, cross‐sectional study. Methods Outpatients with an ostomy (n = 127) were recruited from proctology, wound and stoma therapy unit and general surgery clinics between January and 28 March 2020. The data were collected using the Socio‐demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…The results of this study showed that religious belief and educational background were the influencing factors of spiritual care needs, and patients with religious belief and high educational background had high spiritual care needs, which was similar to the results of previous studies (Forouzi et al, 2017;Cheng et al, 2018;Ayik et al, 2021). The reasons may be as follows: First, religious belief is an important part of spiritual care needs, which is an expression of spirituality, at the highest level of spiritual conceptual framework, and its expression forms mainly include participating in religious activities, reading related books, and so on, seeking integration in the relationships among heaven, human, things, and myself, seeking eternal life meaning and value, and regaining peace and comfort through continuous transcendence and integration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that religious belief and educational background were the influencing factors of spiritual care needs, and patients with religious belief and high educational background had high spiritual care needs, which was similar to the results of previous studies (Forouzi et al, 2017;Cheng et al, 2018;Ayik et al, 2021). The reasons may be as follows: First, religious belief is an important part of spiritual care needs, which is an expression of spirituality, at the highest level of spiritual conceptual framework, and its expression forms mainly include participating in religious activities, reading related books, and so on, seeking integration in the relationships among heaven, human, things, and myself, seeking eternal life meaning and value, and regaining peace and comfort through continuous transcendence and integration.…”
Section: Discussionsupporting
confidence: 92%
“…The American National Consensus Project (ANCP) for Quality Palliative Care (Handzo et al, 2020) pointed out that spirituality is a way for people to find and express the meaning, value, and purpose of life and to experience the connection among themselves, others, supremes (such as Gods or holiness), nature, and beliefs. Spiritual care is to provide individuals with care measures or activities in line with their culture and beliefs by listening, accompanying, or discussing the meaning and value of life with patients according to the assessment results of individual spiritual needs or problems (Ayik et al, 2021). As the core of palliative care and holistic care, spiritual care aims to meet patients’ spiritual needs and alleviate spiritual problems, including helping patients seek meaning and purpose in life when suffering from illness, giving love and forgiveness, and obtaining internal and external resources, so that patients can get peace and comfort (Donesky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Worrying about life and death coupled with the shortage of social support system are more likely to suffer spiritual distress and pain of different degrees of body-mind-society-spirit integrity than young and middle-aged patients, such as anxiety, depression, the self-perceived burden increased, self-efficacy and happiness decreased, and the fear of death (Kim et al, 2015). More importantly, studies have reported that the elderly usually have the need to find the meaning and value of life, hope and strength, forgiveness and other needs, that is, spiritual care needs (Ayik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality is derived from the Latin word “Spiritus,” which means breathing, courage, strength, energy and soul, and usually endowed with the spirit of life (Lazenby, 2010). Spiritual care refers to the provision of care measures or activities for individuals according to their culture and beliefs by listening, accompanying or discussing the meaning and value of life with patients according to the assessment results of individual spiritual needs and pains (Ayik et al, 2021; Johnson et al, 2021). At present, the definition of spiritual care needs has not reached a consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality is derived from the Latin word “Spiritus,” which means breathing, courage, strength, energy, and soul, and usually endowed with the spirit of life, meaning to make life more abundant and vigorous (Lazenby, 2010; Weathers et al, 2016; Green et al, 2020). Spiritual care refers to the provision of care measures or activities for individuals according to their culture and beliefs by listening, accompanying, or discussing the meaning and value of life with patients according to the assessment results of individual spiritual needs and pains (Ayik et al, 2021; Johnson et al, 2021). During spiritual care, nurses can achieve resonance and empathy with patients, help patients explore the value of life and find the meaning of life, and help patients build a healthy body, psychology, and spirituality (Donesky et al, 2020; Musa, 2020).…”
Section: Introductionmentioning
confidence: 99%